Design and implementation of an intelligent home energy management system: A realistic autonomous hybrid system using energy storage. (18th October 2018) - Sami, Ben Slama; Sihem, Nasri; Bassam, Zafar
Abstract: This paper seeks to develop a Smart Home prototype that improves electricity production without interruption to provide comfortable services for users. So, a realistic autonomous hybrid system including PV source with a fuel cell backup system is studied. The system comprises also energy storage devices for safe energy delivery and recovery. To perform the correct system operations and to meet load requirements, an efficient Real Time Embedded System, Energy Management (RT-ES-EM ) is developed and discussed through various tasks of constraints using a new Multi-Agent-System (MAS ). The proposed energy management system aims to define the functions of the agent and to perceive the source situations through the energy demand and the characteristics of the production costs. The results show that the proposed system meets the objectives set for theRT-ES-EM by referring to an experimental database extracted from the Tunisian Meteorological Services using the Matlab/Simulink environment. Highlights: Smart-Home system prototype. Real-Time-Embedded-System Energy Management. Multi-agents strategy for system modeling. Investment cost analysis. Input experimental data parameters from Tunisian sector.